Phytochemical analysis, phytotoxic and alpha amylase inhibition activity of Cyanodondactylon - Sharma, Khaga Raj (Journal of Balkumari College, 2019)
Herbal medicines that obtained from medicinal plants are safe and oldest natural products used for treatment of different diseases. The present study was undertaken to evaluate the phytochemical analysis, phytotoxic activity and alpha amylase enzyme inhibition activity of methanolic extract of Cyanodondactylon. For this whole plant was collected and shade dried and grinded to get the powder. The extraction was carried out by cold percolation in methanol. The methanolic extract was subjected to phytochemical analysis for the absence or presence of secondary metabolites using standard protocol. In-vitro phytotoxic activity was performed by adopting the standard protocol. The alpha amylase enzyme inhibition activity of plant extract was carried out by using starch as substrate, pancreatic alpha amylase as the enzyme, and acarbose as standard. Phytochemical analysis displayed the presence of different chemical constituents such as alkaloids, flavonoids, tannins, polyphenols, terpenoids etc. The result of in-vitro phytotoxic bioassay revealed that the plant extract showed moderate activity with percentage growth regulation 75% in 1000 µg/ml and 30% in 10 µg/ml. The alpha amylase enzyme inhibition was 96.2% at 1000 µg/ml while 37.06% at 40 µg/ml concentration. The inhibition was found dose dependent.